On the type specimen of Panochthus Frenzelianus Ameghino, 1889 (xenarthra, glyptodontia, panochthidae) - Fernicola, Juan Carlos (2014)
Panochthus frenzelianus was described by Ameghino in 1889 based on a skull, mandible, cephalic shield, osteoderms from the posteriormost rows of carapace, and caudal rings. Unfortunately, the type specimen was not specified and the provenance and repository of the described specimens were not informed. In 1903, Osborn stated that the holotype of this species was part of a collection of fossil mammals that Cope bought in France in 1878 and later deposited in the AMHN of New York. In 1942, Castellanos published a photograph of the purported holotype of P. frenzelianus (a mounted skeleton) and confirmed that it was deposited at the AMNH, as previously stated by Osborn. However, the specimen presents some differences with the material described in 1889 by Ameghino. Here we attempt to determine the true type specimen of P. frenzelianus and its repository based on information available on the literature, the AMNH collection, archives e.g., notes, catalogs), and on a morphological analysis of some elements assigned to Panochthus housed in that institution. We found that:(1) the specimen figured by Castellanos and exhibited at the AMNH is a composite specimen formed by remains of at least three individuals;(2) these remains do not bear the diagnostic features mentioned by Ameghino and, therefore, they cannot be assigned to the holotype of P. frenzelianus; (3) a cephalic shield and a mandible belonging to another specimen at the AMNH bear the diagnostic characters mentioned by Ameghino, and are the only parts that we could confidently assign to the holotype of P. frenzelianus.